Implementing the Agricultural Biodiversity Programme of Work: The contribution of Bioversity International and its partners - Bioversity International (2008)
Since the adoption of the Programme of Work on Agricultural Biodiversity in 2000 (Decision V/5, annex 5), there has been a substantial expansion of work on the conservation and use of agricultural biodiversity throughout the world. This pamphlet describes the results of a range of collaborative initiatives in over 30 countries, in all regions of the world, involving institutes, organizations, communities and farmers working with Bioversity International. The work focused on the maintenance and use of crop diversity and the conservation of crop wild relatives and has contributed directly to all four elements of the Programme of Work - assessment, adaptive management, capacity building and mainstreaming - and also to the International Initiative on Biodiversity for Food and Nutrition (Decision VIII/23 A, annex). We thank the many international, national and local organizations, farmers and communities throughout the world that have worked with us over the past few years. They have generously shared their experience, knowledge and ideas to implement the collaborative programmes whose results are described in this document.